KONSENTRASI HORMON TESTOSTERON DAN PROFIL DARAH SAPI BALI YANG DIBERI CHROMOLAENA ODORATA, ANALOG HIDROKSI METIONIN DAN MINYAK NABATI (Testosterone hormone concentration and blood profile of bali cows given chromolaena odorata, hydroxy analogues .....) - Gustaf Oematan; Erna Hartatia; M. L. Mullik; N. Taratiba; Twen. O. Dami Dato; G. A.Y. Lestari; Grouse . T.S. Oematan (Universitas Nusa Cendana, 2023)
The study aims to investigate the influence of supplementation of hydroxy methionine analogues (HMA) and vegetable oils (VO) on testosterone hormone levels and physiological profile of blood plasma of fattening Bali cattle. A randomized block design with four treatments and four tests was used in the study. Sixteen male Bali cattle with a body weight range of 78-183 kg with CV of 25.33% were used. The ration containeds 18% protein and ME = 16 MJ/kg DM with a target weight gain of 0.6 kg/day. The ration is prepared with a protein content of 18% and metabolic energy = 16 MJ / kg BK with a target of weight gain of 0.6 kg / day. Concentrate is given as much as 3% of body weight while rice straw and drinking water are provided ad libitum. The treatment were as follows: RA = concentrate containing C. odorata flour + rice straw ad libitum (control); RB = RA + 3 g HMA; RC = RA + 0.5% VO and RD = RA + 3 g HMA + 0.5% VO. The variables measured were as follows: testosterone hormone, erythrocytes, hemoglobin, leucocytes and hematocrit. The results showed that the supplementation of HMA and VO had no significant effect (P˃0.05) on testosterone hormone levels and physiological profile of blood plasma of the study livestock. It was concluded that the use of AHM and VO had no impact on changes in testosterone hormone concentrations and blood profiles of study cattle